Bonding capacity of GFRP sheet for concrete beams strengthening under saline water environment - Amir Sultan, Mufti; Djamaluddin, Rudy (International Journal of Engineering and Technology, 2018)
Structures built in aggressive environments such as in the sea/marine environment need to be carefully designed, due to the possibility of chloride ion penetration into the concrete. One way to reduce the strength degradation in such environment is to use FRP, which isÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â attached to the surface of reinforced concrete using epoxy. A series of the specimen of reinforced concrete beams with dimension 100Ã—120Ã—600 mm were cast. Beams were immersed in the saline water for 3 months (B3), 6 months (B6) and 12 months (B12). Three specimens were prepared to control beam without immersion in the saline water (B0). Write the study presented is focused on determining the effect of the saline water environment to the capacity of GFRP as flexural external reinforcement elements. The result indicated that the bonding capacity of B3, B6, and B12 compared to B0 decrease of 7.91%, 11.99%, and 37.83% respectively. The decreasing was caused by the weakening of the bonding capacity GFRP due to the influence of the saline water environment.Â